Widespread expression of intestinal markers in gastric carcinoma: a light and electron microscopic study using BD-5 monoclonal antibody. Issue 2 (February 1988) - Fiocca, R; Villani, L; Tenti, P; Cornaggia, M; Finzi, G; Capella, C; Prat, M; Bussolati, G; Solcia, E
Abstract : BD-5 monoclonal antibody reacted with tumour cells in 262 of 316 cases of gastric cancers, including 121 of 134 early, 141 of 182 advanced tumours (p less than 0.01), and 113 of 146 glandular, 72 of 83 diffuse, 22 of 25 mucoid, and 55 of 59 mixed tumours. No difference in reactivity was observed between metastatic and non-metastatic advanced tumours. Immunocytochemical techniques applied to light and electron microscopical specimens of colorectal mucosa and gastric cancer showed that BD-5 immunoreactive material occurred in the Golgi complex, in small clear, to dense cored, cytoplasmic vesicles, and in the glycocalix of the luminal and lateral membranes of normal and neoplastic cells in the glands, as well as in the peripheral membrane of dispersed neoplastic cells. Mucin granules stored in the cytoplasm of goblet cells were unreactive or poorly reactive. Ultrastructural features consistent with colorectal type differentiation were observed in many reactive tumours. Unreactive tumours showing ultrastructural patterns consistent with intestinal differentiation, especially of small bowel type, were also observed. Signs of intestinal differentiation, including BD-5 immunoreactivity, often occur in gastric cancer, irrespective of histological type and stage of disease.